Peculiar features of the plastids of the colourless alga Euglena longa and photosynthetic euglenophytes unveiled by transcriptome analyses - Záhonová, Kristína; Füssy, Zoltán; Birčák, Erik; Novák Vanclová, Anna M G; Klimeš, Vladimír; Vesteg, Matej; Krajčovič, Juraj; Oborník, Miroslav; Eliáš, Marek (Scientific reports, 2018)
Euglenophytes are a familiar algal group with green alga-derived secondary plastids, but the knowledge of euglenophyte plastid function and evolution is still highly incomplete. With this in mind we sequenced and analysed the transcriptome of the non-photosynthetic species Euglena longa. The transcriptomic data confirmed the absence of genes for the photosynthetic machinery, but provided candidate plastid-localised proteins bearing N-terminal bipartite topogenic signals (BTSs) of the characteristic euglenophyte type. Further comparative analyses including transcriptome assemblies available for photosynthetic euglenophytes enabled us to unveil salient aspects of the basic euglenophyte plastid infrastructure, such as plastidial targeting of several proteins as C-terminal translational fusions with other BTS-bearing proteins or replacement of the conventional eubacteria-derived plastidial ribosomal protein L24 by homologs of archaeo-eukaryotic origin. Strikingly, no homologs of any key component of the TOC/TIC system and the plastid division apparatus are discernible in euglenophytes, and the machinery for intraplastidial protein targeting has been simplified by the loss of the cpSRP/cpFtsY system and the SEC2 translocon. Lastly, euglenophytes proved to encode a plastid-targeted homolog of the termination factor Rho horizontally acquired from a Lambdaproteobacteria-related donor. Our study thus further documents a substantial remodelling of the euglenophyte plastid compared to its green algal progenitor.
Keywords: Evolution, Molecular; Sequence Homology; plastidy; fylogeneze; Euglena longa; Chloroplast Proteins; Photosynthesis; Plastids; fotosyntéza; sekvenční homologie; Base Sequence; proteiny chloroplastové; Gene Expression Profiling; Phylogeny; stanovení celkové genové exprese; sekvence nukleotidů; molekulární evoluce